Analysis of risk factors for occlusions of a synthetic femoropopliteal bypass graft - Mirković, Nikola; Stefanović, Srdjan; Janković, Slobodan (Vojnosanitetski pregled, 2015)
Background/Aim. Femoropopliteal bypass is a revascularization technique of lower extremities with excellent outcome. The great saphenous vein is the best graft material, but if it is not adequate or has been removed, synthetic grafts are an useful alternative. Graft occlusion is the most significant complication with the most serious consequences. The aim of this study was to analyse predictive factors for the synthetic femoropopliteal bypass occlusions. Methods. This retrospective case-control study included all patients who underwent synthetic femoropopliteal bypass due to peripheral arterial occlusive disease at the Vascular Surgery Center, Clinical Center of Kragujevac, Serbia, from 2007 to 2013. The cases group were the patients with femoropopliteal graft occlusion (n = 44), with the control group consisted of the patients without such an outcome (n = 88). Results. Significant effects to occlusion were: concomitant cardiovascular disease (adjustedOR 27.05; 95% CI 4.74; 154.35), a type of femoropopliteal bypass (adjustedOR 16.50; 95% CI 4.05; 67.24), previous vascular intervention (adjustedOR 4.67; 95% CI 1.20; 18.14), clinical stage of the disease (adjustedOR 3.73; 95% CI 1.94; 7.18), administration of postoperative oral anticoagulant therapy (adjustedOR 0.05; 95% CI 0.01; 0.23) and the use of angiotensin converting enzyme inhibitors (adjustedOR 0.14; 95% CI 0.03; 0.70). A significant synergism was shown for the following combinations of the observed risk factors: type of femoropopliteal bypass and cardiovascular disease, type of femoropopliteal bypass and previous vascular intervention, previous vascular intervention and cardiovascular disease, previous vascular intervention and beta blockers, cardiovascular disease and diabetes, type of femoropopliteal bypass and antiaggregant therapy, clinical stage of disease and cardiovascular disease, previous vascular intervention and antiaggregant therapy. Conclusion. Concomitant cardiovascular disease, below-knee femoropopliteal bypass, advanced stage of vascular disease and non-use of anticoagulant therapy and angiotensin-converting enzyme inhibitors are the significant predictors of graft occlusion after synthetic femoropopliteal bypass. Their synergistic effect determines the importance of diabetes, use of beta blockers and platelet antiaggregant therapy.
Keywords: graft occlusion; vascular; biocompatible materials; femoral artery; saphenous vein; risk factors